Learning Profile at SD 3 Banjar Sari During the Covid-19 Pandemic - Linda Feni Haryati; Nursaptini Nursaptini (Educatio, 2020)
Indonesia began to be affected by Covid-19 in early 2020, of course, this will give changes to all sectors of life. One sector that has also felt the impact is the education sector. On March 24, 2020, the Minister of Education and Culture of the Republic of Indonesia issued a government circular number 4 of 2020 concerning the Implementation of Education Policy in an Emergency for the Spread of COVID, by stipulating the provisions of the teaching and learning process starting from tertiary to basic education levels to be carried out online or learning at home. This distance learning course provides new challenges for teachers, students, and parents, in its implementation. This research aims to find out more clearly how the distance learning process and what obstacles are faced by teachers, students, and parents at SDN 3 Banjar Sari during the Covid-19 Pandemic. The method used in this research is qualitative research methods. This type of research uses a multi-case study design. Research results: the teacher has tried to do several learning methods, but until now there is no method that is considered the most effective in the teaching and learning process during the Covid-19 pandemic. Each method used by the teacher does not escape from various obstacles and shortcomings. Even so, teachers still try their best to carry out their duties in order to realize the goals of education.